Origin and evolution of oilfield waters in the Tazhong oilfield, Tarim Basin, China, and their relationship to multiple hydrocarbon charging events. (December 2018) - Chen, Jian; Liu, Dayong; Hou, Xiaolin; Fan, Yukun; Jia, Wanglu; Peng, Ping'an; Zhang, Baoshou; Xiao, Zhongyao
Abstract: We conducted a chemical and isotopic study of oilfield waters from Ordovician limestone reservoirs in the Tazhong oilfield (Tarim Basin, China) to trace the origin and evolution of the waters, and to demonstrate their possible relationship with hydrocarbon charging. The elemental chemistry (Cl, Br, SO4, I, K, Na, Ca, Mg, and Sr) and multiple isotopic compositions (δD, δ 18 O, 87 Sr/ 86 Sr, and 129 I/I) of the oilfield waters were determined. The results show that these oilfield waters contain basinal brines that infiltrated in three stages, along with a lesser contribution from meteoric water. The meteoric water appears to have infiltrated downwards during the late Silurian and Carboniferous. The earliest brine had very low I contents (<5.65 mg/L) and migrated upwards from organic-poor Cambrian to Lower Ordovician dolostones during the Late Ordovician. The second brine had high I contents (>50 mg/L), was derived from Cambrian argillaceous source rocks, and migrated upwards into Ordovician reservoirs. This stage was related to the main period of migration of crude oils out of the source rocks into reservoirs during the Silurian and Devonian. Both of these brines incorporated constant levels of fissiogenic 129 I from the limestone reservoir rocks (11.8–47.0 atom/μL). Finally, brine with very low I contents, but higher 129 I (106–491 atom/μL), began to migrate upwards and infiltrate reservoirs. Given the relatively high fissiogenic 129 I, this stage may have occurred during the late Cenozoic, and was associated with migration of dry gas from the same source rocks. Our results, combined with those of a previous study of other oilfields in the basin, suggest that the evolutionary of oilfield waters can be used to constrain hydrocarbon accumulation events, and both of which were ultimately controlled by regional tectonism and local geological factors. Highlights: The oilfield waters comprise three brine types and meteoric water. The evolution of oilfield waters was closely related to hydrocarbon accumulation. Composition and evolution of oilfield waters were controlled by regional tectonism.